A T-shaped 1 × 8 balanced optical power splitter based on 90° bend asymmetric vertical slot waveguides. (12th March 2019) - Butt, M A; Khonina, S N; Kazanskiy, N L
Abstract: We proposed a T-shaped 1  ×  8 balanced optical power splitter (OPS) design. The working principle of the OPS is based on the coupled-mode theory. Vertical silicon slot waveguides are utilized in the design, which offers optical confinement in transverse electric-polarization. The layout of the OPS is distinctive and provides four output ports, with each on two sides of the chip. Moreover, the bending losses of the waveguides are reduced by ~80% by shifting the slot towards the outer periphery of the bend compared to the symmetric slot waveguide. Numerical investigations suggested that this device can work across the whole C-band, with a maximum of 43% power decay.